Pre- and Postnatal Calorie Restriction Perturbs Early Hypothalamic Neuropeptide and Energy Balance - Shin, Bo-Chul (2012)
Energy balance is regulated by circulating leptin concentrations and hypothalamic leptin receptor (ObRb) signaling via STAT3 but inhibited by SOCS3 & PTP1B. Leptin signaling enhances anorexigenic neuropeptides and receptor (POMC, MC3-R, MC4-R) activation while suppressing orexigenic neuropeptides (NPY, AgRP). We investigated in a sex-specific manner the early (PN2) and late (PN21) postnatal hypothalamic mechanisms in response to intrauterine (IUGR), postnatal (PNGR) and combined (IPGR) calorie and growth restriction. At PN2, while both male and female IUGR were hypoleptinemic, hypothalamic leptin signaling in females was activated as seen by enhanced STAT3. In addition, increased SOCS3 and PTP1B supported early initiation of leptin resistance in females that led to elevated AgRP but diminished MC3-R and MC4-R. In contrast, males demonstrated leptin sensitivity seen as a reduction in PTP1B and MC3-R and MC4-R with no effect on neuropeptide expression. At PN21 with adequate postnatal caloric intake, a sex-specific dichotomy in leptin concentrations was seen in IUGR with euleptinemia in males indicative of persisting leptin sensitivity and hyperleptinemia in females consistent with leptin resistance, both with normal hypothalamic ObRb signaling, neuropeptides and energy balance. In contrast, superimposition of PNGR upon IUGR (IPGR) led to diminished leptin concentrations with enhanced PTP1B and an imbalance in arcuate nuclear NPY/AgRP and POMC expression that favored exponential hyperphagia and diminished energy expenditure post-weaning. We conclude that IUGR results in sex-specific leptin resistance mainly observed in females while PNGR and IPGR abolish this sex-specificity setting the stage for acquiring obesity after weaning.